Answer:
The answer is 76.
Step-by-step explanation:
≅ means to be equal to.
☆Angle DGE ≅ EGF.
Therefore, 3x + 8 = 5x - 12
☆Let's solve that equation.
![3x + 8 = 5x - 12 \\ \frac{ - 5x \: \: \: \: \: \: \: = - 5x \: \: \: \: \: \: \: \: }{ - 2x + 8 = - 12} \\ \frac{ \: \: \: \: \: \: \: \: - 8 = - 8}{ \frac{ - 2x}{ - 2} = \frac{ - 20}{ - 2} } \\ x = 10](https://tex.z-dn.net/?f=3x%20%20%2B%208%20%3D%205x%20-%2012%20%5C%5C%20%20%5Cfrac%7B%20-%205x%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%20%3D%20%20-%205x%20%20%5C%3A%20%20%5C%3A%20%20%20%5C%3A%20%20%5C%3A%20%20%20%5C%3A%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%7D%7B%20-%202x%20%2B%208%20%3D%20%20-%2012%7D%20%20%5C%5C%20%20%5Cfrac%7B%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20-%208%20%20%3D%20%20-%208%7D%7B%20%20%5Cfrac%7B%20-%202x%7D%7B%20-%202%7D%20%20%3D%20%20%5Cfrac%7B%20-%2020%7D%7B%20-%202%7D%20%7D%20%20%20%5C%5C%20x%20%3D%2010)
We found the value of x which is 10.
☆Let's Now plug in.
![DGE \\ 3x + 8 \\ 3(10) + 8 \\ 30 + 8 \\ 38](https://tex.z-dn.net/?f=DGE%20%5C%5C%203x%20%2B%208%20%5C%5C%203%2810%29%20%2B%208%20%5C%5C%2030%20%2B%208%20%5C%5C%2038)
and the other:
![EGF \\ 5x - 12 \\ 5(10) - 12 \\ 50 - 12 \\ 38](https://tex.z-dn.net/?f=EGF%20%5C%5C%205x%20-%2012%20%5C%5C%205%2810%29%20-%2012%20%5C%5C%2050%20-%2012%20%5C%5C%2038)
☆They asked for what the angle of DGF measured. So we would have to add both sides
![38 + 38 = 76](https://tex.z-dn.net/?f=38%20%2B%2038%20%3D%2076)
☆The answer is 76
Answer:
Answer below
Step-by-step explanation:
1/8 is correct
in pic
_________________________________________
(Hope this helps can I pls have brainlist (crown)☺️)
The answer is c.2 I hope it’s right
Answer:
h=![h= \frac{5R^{3} }{LU}](https://tex.z-dn.net/?f=h%3D%20%5Cfrac%7B5R%5E%7B3%7D%20%7D%7BLU%7D)
Step-by-step explanation:
1.) You must isolate the h from the equation by dividing both sides by L (or multiply by its reciprocal, which in this case, the reciprocal on L is
.....So it would look like:
![(\frac{1}{L} )*\frac{5R^{3} }{U} = \frac{L}{h}* (\frac{1}{h} )\\](https://tex.z-dn.net/?f=%28%5Cfrac%7B1%7D%7BL%7D%20%29%2A%5Cfrac%7B5R%5E%7B3%7D%20%7D%7BU%7D%20%3D%20%5Cfrac%7BL%7D%7Bh%7D%2A%20%28%5Cfrac%7B1%7D%7Bh%7D%20%29%5C%5C)
2.) Simplify the equation if you need to (in this case, its not needed)
![\frac{5R^3}{LU} =h](https://tex.z-dn.net/?f=%5Cfrac%7B5R%5E3%7D%7BLU%7D%20%3Dh)
That's your answer :)